The efficacy of pre-emptive dexmedetomidine versus amiodarone in preventing postoperative junctional ectopic tachycardia in pediatric cardiac surgery - Nagat S El-Shmaa; Doaa El Amrousy; Wael El Feky (Annals of Cardiac Anaesthesia, 2016)
Objective: The objective of this study was to assess the effectiveness of pre-emptive dexmedetomidine versus amiodarone in preventing junctional ectopic tachycardia (JET) in pediatric cardiac surgery. Design: This is a prospective, controlled study. Setting: This study was carried out at a single university hospital. Subjects and Methods: Ninety patients of both sexes, American Society of Anesthesiologists Physical Status II and III, age range from 2 to 18 years, and scheduled for elective cardiac surgery for congenital and acquired heart diseases were selected as the study participants. Interventions: Patients were randomized into three groups (30 each). Group I received dexmedetomidine 1 mcg/kg diluted in 100 ml of normal saline intravenously (IV) over a period of 20 min, and the infusion was completed 10 min before the induction followed by a 0.5 mcg/kg/h infusion for 72 h postoperative, Group II received amiodarone 5 mg/kg diluted in 100 ml of normal saline IV over a period of 20 min, and the infusion was completed 10 min before the induction followed by a 10–15 mcg/kg/h infusion for 72 h postoperative, and Group III received 100 ml of normal saline IV. Primary outcome was the incidence of postoperative JET. Secondary outcomes included vasoactive-inotropic score, ventilation time (VT), pediatric cardiac care unit stay, hospital length of stay, and perioperative mortality. Measurements and Main Results: The incidence of JET was significantly reduced in Group I and Group II (P = 0.004) compared to Group III. Heart rate while coming off from cardiopulmonary bypass (CPB) was significantly low in Group I compared to Group II and Group III (P = 0.000). Mean VT, mean duration of Intensive Care Unit stay, and length of hospital stay (day) were significantly short (P = 0.000) in Group I and Group II compared to Group III (P = 0.000). Conclusion: Perioperative use of dexmedetomidine and amiodarone is associated with significantly decreased incidence of JET as compared to placebo without significant side effects.